Serological evidence of continued exposure to Plasmodium falciparum among residents in a near-elimination setting - Daud, Muhammad Muzhaffar; Rahayu, Aprillia Andika; Ilyas, M.; Hitipeuw, Derico; Fitriana, Fadhila; Syahada, Jadidan Hada; Nuranindita, Raisha; Amirudin, Fariha Akmalina; Saputra, Edo Yungki; Jeon, Bo-Young; Cahyani, Ni Kadek Dita; Pandupuspitasari, Nuruliarizki Shinta; et al. (Frontiers in Microbiology, 2026)
BackgroundMalaria transmission has significantly declined in several endemic regions following extensive control efforts, bringing some areas close to elimination status. However, residual exposure to Plasmodium falciparum may persist even when clinical cases become rare. Serological markers provide valuable insights into historical and recent exposure by detecting long-lived antibodies that remain after infection. The use of blood-stage antigens such as PfEBA175 and PfRh5 allows for assessing population-level immunity and identifying potential hotspots of residual transmission.MethodsA community-based cross-sectional study was conducted from May to June 2025 across four endemic villages (Sedayu, Kemejing, Kembaran, and Wadas) in the Menoreh Hills. Blood samples from 120 malaria-exposed individuals and 24 malaria-negative controls were analyzed using protein microarray to assess antibody responses to PfEBA175 and PfRh5 antigens. Sociodemographic and behavioral risk factors were obtained through structured questionnaires.ResultsSignificant heterogeneity in antibody responses was observed across villages from two antigens. Seropositivity of PfEBA175 was higher than PfRh5. PfEBA175 seroprevalence ranged from 10 to 40%, with significantly higher responses in Kembaran (40%, p < 0.001) and Wadas (23%, p = 0.003) compared with controls, reflecting focalized transmission. PfRh5 demonstrated universal immunogenicity with 53–70% seroprevalence across all villages (p < 0.001), with Sedayu showing the highest responses (70%) linked to nocturnal livestock activities (p = 0.006). Village-specific risk factors including indoor biting exposure, previous malaria history, outdoor nighttime activities, educational level, and travel to endemic areas were significantly associated with antibody profiles, highlighting micro-epidemiological heterogeneity in malaria exposure.ConclusionThis study reveals substantial micro-epidemiological variation in naturally acquired immunity to blood-stage malaria antigens in a pre-elimination setting. PfRh5 demonstrated universally strong immunogenicity across transmission intensities, whereas PfEBA175 exhibited heterogeneous responses reflecting focal exposure shaped by behavioral and environmental factors. These complementary patterns may inform multi-antigen vaccine strategies, village-specific interventions in areas with residual malaria transmission, and sero-surveillance development.